PENDIDIKAN KESEHATAN TENTANG TB PARU PADA USIA PRODUKTIF (24 – 44 TAHUN) DI WILAYAH KERJA PUSKESMAS UNIT 2 RIMBO BUJANG PROVINSI JAMBI - Hani Ruh Dwi (JURNAL KREATIVITAS PENGABDIAN KEPADA MASYARAKAT (PKM), 2018)
ABSTRACT Health status is a problem that must be considered by each individual citizen. In Indonesia Pulmonary TB is a disease that is a scourge for society, the high incidence of pulmonary TB is a familiar phenomenon. One of the burdens of pulmonary TB is social interaction in society, this is caused by lack of knowledge. The purpose of the activities of residents can understand about Lung TB. The activity will be held on Saturday 4th August 2018. The activity was carried out by means of health education for the residents about Pulmonary TB in the working area of Rimbo Bujang unit 2 health center with health education method using power points and leaflets. Based on the activities there were significant results on the knowledge of the residents before and after being given health education about pulmonary TB. This activity provides positive results for residents in the Rimbo unit 2 Puskesmas working area about Pulmonary TB. Keywords: Pulmonary TB, Productive Age, Health Education